Brachytherapy practice during the COVID-19 pandemic: a review on the practice changes - Barthwal, Mansi; Pareek, Vibhay; Mallick, Supriya; Sharma, D (Journal of Contemporary Brachytherapy, 2020)
The COVID-19 pandemic has caused a havoc across the globe, and has significantly affected oncology services, especially radiation therapy due to the need of social distancing as a measure for the pandemic mitigation. Brachytherapy, being an integral part of radiation therapy, posts a dilemma related to the practice of evidence-based oncology. It requires a significant amount of resources and personnel, thereby increasing the risk of exposure to the virus. There has been a significant amount of papers published providing the best available alternatives to external radiation; however, there is a lack of literature on the practice of brachytherapy. In times of the pandemic, deploying brachytherapy as a treatment modality can act as a double-edged sword and therefore, judicious use is warranted in such times of crisis. In this article, we provide a comprehensive review of the role of brachytherapy in various forms and different malignancy sites.